2021
DOI: 10.1111/1346-8138.16035
|View full text |Cite
|
Sign up to set email alerts
|

Clinical effectiveness of efinaconazole 10% solution for treatment of onychomycosis with longitudinal spikes

Abstract: Onychomycosis with longitudinal spikes in the nail plate has been reported to be refractory to oral drugs as with dermatophytoma. We evaluated the efficacy of 10% efinaconazole solution in the treatment of onychomycosis with longitudinal spikes. Of the 223 subjects who were enrolled in a previous study, a post‐hoc analysis of 82 subjects with longitudinal spikes was performed in this study. The opacity ratio of longitudinal spikes was decreased over time from 8.1 to 0.9 at the final assessment. In addition, th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 19 publications
0
6
0
Order By: Relevance
“…Despite lower cure rates, topical monotherapy is recommended in mild toenail onychomycosis limited to the distal nail, as well as WSO. Recent data, however, show that efinaconazole can be very effective in treating onychomycosis complicated by dermatophytomas and longitudinal spikes [51,52].…”
Section: Treatment Approachmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite lower cure rates, topical monotherapy is recommended in mild toenail onychomycosis limited to the distal nail, as well as WSO. Recent data, however, show that efinaconazole can be very effective in treating onychomycosis complicated by dermatophytomas and longitudinal spikes [51,52].…”
Section: Treatment Approachmentioning
confidence: 99%
“…Poor response to treatment is seen at higher rates in individuals with subungual keratosis measuring more than 2 mm and fungal infection involving the lateral nail or over 50% of the entire nail unit [15]. Recently a few studies showed that topical treatment with efinaconazole can be useful in this setting [51,52]. Given the terbinafine sensitivity to dermatophytes, onychomycosis caused by mixed infection or resistant organisms are also associated with poor prognostic outcomes.…”
Section: Oral Treatmentsmentioning
confidence: 99%
“…As reports of terbinafine resistance increased, the need for alternative therapies also increased. In contrast to the traditional therapies, the latest generation of topical therapies, (e.g., tavaborole, efinaconazole, and luliconazole) designed with improved transungual nail plate penetration chemistry as well as direct subungual penetration have shown promising efficacy for dermatophytomas without the need for concomitant debridement or avulsion ( Table 1 ) [ 24 , 28 , 37 , 38 , 39 ]. Fosravuconazole is currently the only product of the newer generation of oral antifungals tested for dermatophytomas.…”
Section: Current Treatment Optionsmentioning
confidence: 99%
“…Despite issues of drug penetration with topical treatments, efinaconazole 10% solution, a triazole antifungal targeting ergosterol biosynthesis causing cell membrane disruption, has shown promising results albeit with a variable success rate (<25% to 100%) with once-daily treatment duration up 48 weeks [ 24 , 38 , 39 ]. The efficacy of the efinaconazole solution may be related to the high degree of penetration through the transungual route.…”
Section: Current Treatment Optionsmentioning
confidence: 99%
See 1 more Smart Citation